ACADEMIC LEADERSHIP OF SCHOOL ADMINISTRATORS AFFECTING THE INTERNAL QUALITY ASSURANCE PROCESS IN SCHOOLS UNDER THE KHLONG SAM WA DISTRICT OFFICE BANGKOK METROLITAN - สุมาลัย กมลทิพย์; แก้วมงคล ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were: 1) To study the academic leadership of school administrators under the Khlong Samwa District Office, Bangkok 2) To study the academic leadership of school administrators under the Khlong Sam Wa District Office, Bangkok. 3) To study the internal quality assurance operations of educational institutions under the Khlong Sam Wa District Office, Bangkok. 4) To study the relationship between the academic leadership of school administrators and the internal quality assurance operations of educational institutions under the Khlong Sam Wa District Office, Bangkok. To study the academic leadership of school administrators that affects the internal quality assurance operations of schools under the Khlong Sam Wa District Office, Bangkok, the research sample included administrators and teachers of schools under the Khlong Sam Wa District Office, Bangkok, for the academic year 2025. A total of 250 samples were obtained thru simple random sampling. The data collection instrument was a Likert-scale questionnaire with a reliability of 0.98. The statistics used for data analysis included percentage, mean, standard deviation, Pearson Product Moment Correlation, and Stepwise Multiple Regression Analysis. The research findings revealed that: • The academic leadership of school administrators under the Khlong Sam Wa District Office, Bangkok, overall, is rated at a high level. • The implementation of internal quality assurance in educational institutions under the Khlong Sam Wa District Office, Bangkok, overall received a high level of agreement. • The relationship between the academic leadership of school administrators and the internal quality assurance operations of schools under the Khlong Sam Wa District Office in Bangkok is overall at a moderate level (r = .690) with statistical significance at the .01 level. 4. Factors affecting the implementation of internal quality assurance in educational institutions include the management of curricula and teaching (X5), which has a statistically significant relationship with the implementation of internal quality assurance at the .01 level. This factor can predict academic management in educational institutions by 47.58 percent.